2020
DOI: 10.3280/efe2020-001003
|View full text |Cite
|
Sign up to set email alerts
|

Policy measures for electric vehicle adoption. A review of evidence from Norway and China

Abstract: Purpose To mitigate energy and environmental challenges, several countries worldwide are considering different policies to promote the use of electric vehicles (EVs). Consequently, the necessity of studies focusing on the important and effective EV policy measures are develop-ing as policymakers are seeking to prioritize the policy measures based on their usefulness to achieve mass EV adoption. This study reviews evidence from China and Norway to identify factors that could substantially accelerate demand for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Indonesia can learn from other countries that have shifted from conventional to electric vehicles by integrating electric vehicle-related policies into the national transportation policy. Several studies found that the increase in EV sales since 2009 was mainly due to policy support from the government in the early stages of EV market penetration, such as in China and Norway (Mathisen & Terje, 2020).…”
Section: Recommendations For Scaling Up Electric Vehicles To Reduce C...mentioning
confidence: 99%
“…Indonesia can learn from other countries that have shifted from conventional to electric vehicles by integrating electric vehicle-related policies into the national transportation policy. Several studies found that the increase in EV sales since 2009 was mainly due to policy support from the government in the early stages of EV market penetration, such as in China and Norway (Mathisen & Terje, 2020).…”
Section: Recommendations For Scaling Up Electric Vehicles To Reduce C...mentioning
confidence: 99%